ALGORITHM FOR CREATING A WEB PLATFORM FOR THE INDEPENDENT LEARNING ACTIVITIES OF STUDENTS OF THE ACADEMIC LYCEUMS OF THE MINISTRY OF INTERNAL AFFAIRS (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article presents proposals and recommendations on the algorithm for creating and implementing a web platform designed to organize the independent learning activities of students of the academic lyceums of the Ministry of Internal Affairs.